The dual digestion of sewage sludge using air and pure oxygen - Pitt, Andrew James; Pitt, Andrew James (Urban Water Management, 2017)
Dual Digestion is a two-stage system that combines autothermal thermophilic aerobic pre-treatment with conventional anaerobic digestion. The practicability of the system using pure oxygen is well proven. Disadvantages are the high cost of the pure oxygen and the absence of a detailed evaluation of anaerobic digester performance. This report discusses the results of a full-scale investigation into the dual digestion system (184m³ aerobic reactor and 1800m³ anaerobic digester), carried out in two phases: In the first using air alone for oxygenating the aerobic reactor and in the second using a combination of air and pure oxygen. During both phases the performance of the anaerobic digester was also monitored, but in greater detail in the second phase as far as the final sludge product is concerned. In phase I, with air, it was possible to maintain thermophilic temperatures in the aerobic reactor throughout the year. However, the required retention times were relatively long (3-6 days) in comparison with the pure oxygen reactor (~1 day) due to the high vapour heat losses. At long retention times, the volatile solids (VS) destruction was appreciable (~25%) and the reactor tended towards an autothermal thermophilic digester. Foaming, although unpredictable in its occurrence, significantly improved aerobic reactor performance by doubling the oxygen transfer efficiency. From liquid and gas mass and heat balances it was found that the specific biological heat yield and respiration quotient were approximately constant at 12.8 MJ/kg(O₂) and 0. 70 mol(CO₂)/mol(O₂) respectively over a wide range of operating conditions and consistent relationships between VS removal, heat generation, and oxygen utilisation could be established. Based on information collected, it was concluded that increased treatment capacity and greater temperature control of the aerobic reactor could be provided by supplementing air oxygenation with pure oxygen. In phase II, using a combination of air and pure oxygen, much higher loading rates on the aerobic reactor were possible. Thermophilic temperatures could be maintained at short retention times (1-2 days). Unfortunately, no foaming occurred during this period. Consequently, the benefit of improved oxygen transfer efficiency of the air oxygenation system, produced by the foam, could not be exploited. Liquid and gas mass and heat balances confirmed the specific heat yield and respiration quotient values and the relationship between oxygen utilisation, VS destruction and biological heating. During phase II, the anaerobic digester operated at a retention time of ~10 days. The sensible heat content of the hot sludge from the aerobic reactor was sufficient to force the digester into the thermophilic temperature range. The stability of the anaerobic process and final sludge product at this short retention time was monitored with % VS removal and residual specific oxygen utilisation rate tests and found to be similar to that of conventional mesophilic anaerobic digestion at 20 days retention time. Dewaterability as reflected by the specific resistance to filtration (SRF) was found to be poor, but 11ot much worse than for conventional mesophilic digestion. Sufficient information was obtained during phases I and II to allow a mathematical model to be compiled, which could reasonably reliably simulate all the main operating parameters of the dual digestion system. The model provided a means for assessing different system configurations with mesophilic or thermophilic digestion, with and without heat exchange or gas engine external heat sources, allowing technical and economical (capital and operating) feasibility to be evaluated and compared with that for conventional digestion. From both the experimental and modelled results, all the claimed benefits of the dual digestion system were verified with the exception of the claim that aerobic reactor heat pre-treatment of the sludge allows the anaerobic digester to operate at short retention times (~10 days). However, the digester can be operated at 10 days retention provided its temperature is in the thermophilic range, in which case a sufficiently stable sludge is produced; at mesophilic temperatures, a retention time of 15 days or longer is required to produce a sludge of equivalent stability to that from conventional mesophilic digestion. Consequently, it is not the stability of the anaerobic process per se that governs the minimum retention time but the quality required for the final sludge product. The aerobic reactor is an appropriate pre-treatment stage for the thermophilic digester because it provides the necessary temperature and pH buffering to allow stable operation in the thermophilic range. It is concluded that where application of conventional anaerobic digestion is contemplated, whether for new installations or for upgrading existing plants, the dual digestion system should be seriously considered as a possible option. It competes favourably both technically and economically with conventional mesophilic digestion and produces a superior sludge product which can be beneficially utilised in agriculture.